Influence of NAA and coconut water with variation of soaking duration on the growth of yellow bamboo branch cutting - TIA SETIAWATI; AGINTA PUTRI REHULINA KELIAT; RULY BUDIONO; RUHYAT PARTASASMITA; JOHAN ISKANDAR (Nusantara Bioscience, 2018)
Setiawati T, Keliat APR, Budiono R, Partasasmita R, Iskandar J. 2018. Influence of NAA and coconut water with variation of soaking duration on the growth of yellow bamboo branch cutting. Nusantara Bioscience 10: 178-182. Yellow bamboo (Bambusa vulgaris Schrad Ex. var. Striata) is one kind of bamboo used for industrial and household raw materials. Yellow bamboo propagation with branch cuttings has relatively low percentage of growth. To increase the growing success of yellow bamboo branch cuttings can be used growth regulators substance, such as NAA and coconut water. This study aimed to obtain the best combination of NAA and coconut water with the soaking duration in the growth of yellow bamboo branch cuttings. The study was conducted using Completely Randomized Design (CRD) of 6 × 3 factorial arrangement with five replications. The first factor was the combination of NAA and coconut water (CW), which consisted of six levels, namely 100% CW, 20% NAA + 80% CW, 40% NAA + 60% CW, 60% NAA + 40% CW, 80% NAA + 20% CW and 100% NAA. The second factor was the soaking duration which consists of three levels, namely 12 h, 24 h, and 36 h. Parameters observed included shoot emerging time, shoot number, shoot length, leaf area, root number and root length. The data obtained were analyzed using the Analysis of Variance (ANOVA) and Duncan's Multiple Range Test (DMRT) ?=5%. The results showed that the combination of 80% NAA + 20% CW gave the best yellow bamboo branch cuttings growth with an average shoot length of 1.44 cm, leaf area 41.29 cm2, root number 42.87 and root length 23.70 cm. The interaction of 80% NAA + 20% CW with soaking duration of 36 h resulted in average the fastest shoot emerging time of 2.02 days after planting.